Postural defects - correct posture, pathological posture, pathogenesis and consequences. Part one - Piotr Jaworski (Kazimierz Wielki University, 2019)
Posture defects are a serious social problem. Knowing the correct posture is very important. The first part of the paper presents a description of correct posture and a description of pathological posture, its pathogenesis and side effects.